Managing civil-military cooperation : a 24/7 joint effort for stability - Rietjens, S. J. H.; Bollen, Myriame T. I. B. (Aldershot, England ; Burlington, VT : Ashgate Pub. Company, 2008)
"The varying types of cooperation between the military and a wide range of civilian actors are addressed in this volume. It analyses civil-military cooperation in different settings such as during emergency relief operations (tsunami, earthquakes and refugee crises) and during stability and reconstruction operations such as in Afghanistan and the Democratic Republic of Congo. This book contains contributions from both senior academics and practitioners such as military officers and humanitarian personnel and looks at issues such as what is to be gained by civil-military cooperation. It ends with conclusions and recommendations for both academics and practitioners making it a valuable read for people involved in these operations."--BOOK JACKET.
Includes bibliographic references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Civil-military relations; Comparative government; Electronic books